Displacement of teeth without and with bonded fixed orthodontic retainers: 3D analysis using triangular target frames and optoelectronic motion tracking device. (September 2018) - Chakroun, Firas; Colombo, Vera; Lie Sam Foek, Dave; Gallo, Luigi Maria; Feilzer, Albert; Özcan, Mutlu
Abstract: Purpose: The objective of this study was to evaluate the anterior tooth movement without and with bonded fixed orthodontic retainers under incremental loading conditions. Materials and methods: Six extracted mandibular anterior human teeth were embedded in acrylic resin in True Form I Arch type and 3D reconstruction of Digital Volume Tomography (DVT) images (0.4 mm 3 voxels) were obtained. The anatomy of each tooth was segmented and digitally reconstructed using 3D visualization software for medical images (AMIRA, FEI SVG). The digital models of the teeth were repositioned to form an arch with constant curvature using a CAD software (Rhinoceros) and a base holder was designed fitting the shape of the roots. The clearance between the roots and their slot in the holder was kept constant at 0.3 mm to replicate the periodontal ligament thickness. The holder and the teeth were then manufactured by 3D printing (Objet Eden 260VS, Stratasys) using a resin material for dental applications (E = 2–3 GPa). The 3D-printed teeth models were then positioned in the holder and the root compartments were filled with silicone. The procedure was repeated to obtain three identical arch models. Each model was tested for tooth mobility by applying force increasing from 5 to 30 N with 5 N increments applied perpendicular on the lingual tooth surface on the incisal one third (crosshead speed: 0.1 mm/s). The teeth on each model were first tested without retainer (control) and subsequently with the bonded retainers (braided bonded retainer wire; Multi-strand 1 × 3 high performance wire, 0.022″ × 0.016″). Tooth displacement was measured in terms of complicance (F/Δ movement) (N/mm) using custom-built optoelectronic motion tracking device (OPTIS) (accuracy: 5 µm; sampling rate: 200 Hz). The position of the object was detected through three LEDs positioned in a fixed triangular shape on a metal support (Triangular Target Frame). The measurements were repeated for three times for each tooth. Data were analyzed using mixed model with nesting (alpha = 0.05). Results: The use of retainer showed a significant effect on tooth mobility (0.008 ± 0.004) compared to non-bonded teeth (control) (0.014 ± 0.009) (p < 0.0001). The amount of displacement on the tooth basis was also significantly different (p = 0.0381) being the most for tooth no. 42 (without: 0.024 ± 0.01; with: 0.012 ± 0.002) (p = 0.0018). No significant difference was observed between repeated measurements (p = 0.097) and the incremental magnitude of loading (5–30 N: 0.07 ± 0.01–0.09 ± 0.02) (p > 0.05). Conclusion: Mandibular anterior teeth showed less tooth mobility when bonded with stainless steel wire as opposed to non-bonded teeth but the tooth mobility varied depending on the tooth type. Intermittent increase in loading from 5 to 30 N did not increase tooth displacement.